Single Nucleotide Polymorphism of Interleukin-28β Subunit Genes Predict Host Susceptibility to Hepatitis C virus (HCV) Infection among Iraqi Patients - Hussein, Sahib A.; Al-azzawi, Raghad H. (Iraqi Journal of Science, 2024)
Hepatitis C virus (HCV) is a liver disease that affects14 million people. Feasible research was conducted for identifying the genotypes and allele frequency of some single nucleotide polymorphisms (SNPs) of the IL-28β genes and their predictive role in disease incidence in Iraqi patients. The SNPs (rs28416813, rs4803219, rs11881222, and rs8103142) of IL-28β have been associated with susceptibility to several diseases. Ninety eight (98) HCV patients were included in this research; with average age ± SE (42.28 ± 3.44) years. Also, 80 healthy people (with average age ± SE (29.40 ± 2.84) years) were included as a control group. The SNPs were detected by allele-specific PCR (polymerase chain reaction) using specific primers. The results showed that IL-28β rs28416813 CC genotype was increased in HCV patients significantly while rs4803219 CC and CT genotypes were increased in the HCV patients significantly and insignificantly, respectively. Moreover, rs4803222 GA and AA genotypes frequencies were elevated in HCV patients insignificantly and significantly, respectively. Finally, IL28β rs8103142 gene polymorphism displayed overrepresentation of CT and TT genotypes incidence in hepatitis C patients highly significantly and non-significantly, respectively, as compared to control. The current data suggested that IL28β genetics may have an effect on susceptibility with HCV infection in Iraqis.